Glutamate metabotropic receptors in the lateral hypothalamus/perifornical area reduce the CO 2 chemoreflex - Rodrigues, Laísa Taís Cabral [UNESP]; da Silva, Eliandra Nunes [UNESP]; Horta-Júnior, José de Anchieta C. [UNESP]; Gargaglioni, Luciane H. [UNESP]; Dias, Mirela B. [UNESP] (Elsevier, 2019)
It has been shown that the lateral hypothalamus/perifornical area (LH/PFA) exerts an important role on arousal-state variations of the central chemoreflex, but the mechanisms that underlie LH/PFA chemoreception are poorly understood. Here we asked whether glutamate inputs on metabotropic receptors in the LH/PFA modulate the hypercapnic ventilatory response. We studied the effects of microinjection of a glutamate metabotropic receptor (mGluR) antagonist ((+)-α-Methyl-4-carboxyphenylglycine; MCPG; 100 mM) and a selective Group II/III mGluR antagonist ((2S)-2-Amino-2-[(1S,2S)-2-carboxycycloprop-1-yl]-3-(xanth-9-yl) propanoic acid; LY341495; 5 mM) into the LH/PFA of conscious rats on ventilation in room air and in 7% CO 2 , during wakefulness and sleep, in the dark and light periods of the diurnal cycle. Microinjection of MCPG and LY341495 increased the hypercapnic ventilatory response in both the light and the dark period during wakefulness, but not during sleep, (p < 0.001). Our data suggest that glutamate, acting on Group II/III metabotropic receptors in the LH/PFA, exerts an inhibitory modulation of the hypercapnic ventilatory response in awake rats.
Keywords: Central chemoreception; Glutamate; Hypercapnia; Hypothalamus; Orexin